Figura y traición en el Libro de Alexandre - Ruiz Mautino, Arturo (2021)
The article explores the possibility and conditions of a figural interpretation of the Libro de Alexandre. It proposes, in line with recent takes on the mester de clerecía masterpiece, that treason, as an iterative event and as a moral nucleus of the poem, configures an ideal entry point for apprehending the structure of the text and its poetic self-awareness. We provide a matrix for the scrutiny of the diverse instances of betrayal in the text and we envision a way to assess its validity in contemporary literature written in Spanish.